A survey on 5G capabilities enabling the factories of the future - Yusun FU; Jinhui TANG (Dianxin kexue)
5G systems extend mobile communication services beyond mobile telephony, mobile broadband, and massive machine-type communication into new application domains, so-called vertical domains, with special requirements for communication services.A comprehensive analysis and summary of 5G capabilities enabling the factories of the future were provided, including resilient network architecture, flexible spectrum, ultra reliable and low latency communication, time sensitive network, security and positioning.While resilient network architecture includes network slicing, non-public network, 5G LAN, and edge computing.It hopes to have a thorough and comprehensive understanding of the theoretical research and application of 5G, and a clear understanding of its challenges, so as to play a key reference for researchers and engineers in the related fields.